Etiometry's T3 Heuristic Evaluation. Issue 1 (June 2021) - Meyeroff, Elizabeth; Tremoulet, Patrice
Five students and a Human Factors Psychology professor participated in a heuristic evaluation of clinical decision support software, called T3, to help improve usability. T3 gathers physiological monitoring data from a variety of sources, e.g. pulse oximeters, electrocardiographs, and ventilators, and uses the data to compute two novel risk indexes. To effectively support clinical decision-making, T3 should present the patient data it collects, as well as the risk indexes that it computes, in an easy to understand interactive display. The evaluation identified 38 potential usability issues, about half of which were deemed 'not an issue' or rated as minor. The team developed 11 recommendations for changes to help improve usability of T3. Given the volume and complexity of the information that T3 displays, this is a short list, suggesting relatively good usability. However, none of the evaluators has the clinical training or experience of typical users; it is possible that clinical users would identify additional usability issues.